Pattern of Use of Water Beverage of Hibiscus sabdariffa Linn in a University Community in Southwest Nigeria. (2017)
Background:Water beverages of Hibiscus sabdariffa is widely consumed in many parts of the world. Objective: Its pattern of use in a University community in southwest Nigeria was studied. Methods: A questionnaire-guided survey was conducted among randomly selected staff (398) and students (910) of University of Ibadan on the use of water beverage of Hibiscus sabdariffa (WBHS). The questionnaire garnered information on pattern of use, side effects experienced, and drugs coadministered with WBHS. Descriptive statistics, Chi-square, and Fisher's Exact Probability tests were used to describe the association between categories of participants and indications for using and side effects experienced with WHBS. Results: Most (96.9%) respondents who had used WBHS, used it as a relaxant 382(29.2%), as an antihypertensive 318(24.3%), for weight reduction 140(10.7%), infertility 127(9.7%), to cure liver disease 87(6.7%), and for the management of diabetes 151(11.5%). Side effects experienced with its use were; diarrhea 69(5.3), dizziness 44(3.4%), insomnia 27 (2.1%), decreased libido 24(1.8%), blurred vision 16(1.2%),and headache 19(1.5%).Some of the participants 164(12.5%) coadministered WBHS with their medications such as antibiotics 51(3.9%), antihypertensives 24(1.8%), antipsychotic 18(1.4%), antilipidemic drugs 16(1.2%), and antiretroviral drugs 11(0.8%). Out of those who coadministered WBHS with their medications, 93(7.1%) were on chronic medications. Conclusion: Water beverage of Hibiscus sabdariffa is used to treat diverse diseases with attendant side effects and is sometimes coadministered with medications for chronic diseases. This may predispose users to herb-drug interactions. Thus there is a need to investigate some of the drugs co-administered with the beverage for possible herb-drug interaction.